PERLINDUNGAN HUKUM TERHADAP PERJANJIAN PERKAWINAN ATAS HARTA BERSAMA AKIBAT PERCERAIAN - Nooryanto, Fista Hery; Endah Listyowati, Maria Yosepin; Setyaningrum, Diyah (Universitas Ekasakti, 2023)
The purpose of the study is to identify the legal protection of marital agreements on joint property due to divorce and the benefits of marital agreements as a form of prevention, as well as legal protection of husband and wife's property in the event of divorce. The research method with a normative approach using a conceptual approach analyzes the problem using legal theory and conducts research on legislation that applies and is relevant to the problem. A marriage agreement is considered valid if it is made in writing in the form of a notarial deed before a notary and legalized by the civil registry, namely the KUA for those who are Muslims and a legal entity of citizenship for non-Muslims. Islam. and register with the local District Court, as stated in Chapter V Article 29 Paragraph (I) of the Marriage Law with the Constitutional Court Decision Number 69/PUU-XIII/2015 and its contents also apply to other parties who have an interest. It is concluded that the legal protection of a marriage agreement on joint property due to divorce provides freedom in determining the time for couples to make a marriage agreement and protect their property in the event of a divorce.